TRENDS OF PROFESSIONAL TRAINING OF EXPERTS IN THE FIELD OF EDUCATION IN THE BALKAN COUNTRIES - Tryhub, Ilona I. (Educological discourse, 2017)
The article analyzes the trends of professional training of experts in the field of education in the Balkan countries, such as: Bulgaria, Romania and Hungary. It identified the following common features of professional training of experts in the field of education: focus on quality assurance; implementation of vocational training as part of Continuing Education; seminars and conferences as the basic forms of training; lack of training of experts in the field of education in universities; election of candidates for experts in the field of education from experienced teachers with the experience and good practice; compliance with official Code of Ethics of professional experts in the field of education. International cooperation in quality assurance. Specific trends in training of experts in the field of education in the Balkan countries are not identified.